An Integrated Approach to Detecting Communicative Intent Amid Hyperkinetic Movements in Children. - Lesperance, Andrea; Blain, Stefanie; Chau, Tom (AAC: Augmentative & Alternative Communication, 2011)
Children with hyperkinetic movement (HKM) often have limited access to traditional augmentative and alternative communication technologies (e.g., mechanical switches). To seek a communication solution for these children, this study explored the possibility that discernable biomechanical patterns, related to preference, exist amid HKM. We deployed a unified approach to analyse a child's movements, fusing caregiver and clinician observations with quantitative data (accelerations of the upper extremities). Two case studies were examined. In both, the accelerometer data identified preference at adjusted accuracies statistically above chance using a linear discriminant classifier. Visually, communicative movement patterns were identified in the first child (κ == 0.25-0.27) but not in the second child (κ == 0.03-0.11). Implications of this study include possible enhancement in communication and independence for these children.